A study of the interaction of oxygen with the α2 phase in the model alloy Ti–7wt%Al. (August 2020) - Gardner, H.M.; Radecka, A.; Rugg, D.; Armstrong, D.E.J.; Moody, M.P.; Bagot, P.A.J.
Abstract: Atom Probe Tomography is used to show that the α2 phase (Ti3 Al) forms upon ageing Ti–7Al at 550 °C with as little as 500 wppm oxygen. Notably, it is found that oxygen consistently partitions away from the α2 precipitates to the α matrix. The role of aluminium concentration and oxygen solubility on oxygen partitioning preference is also investigated. Based on our observations, we propose a mechanism by which oxygen encourages α2 formation despite partitioning away from it. Furthermore, nanohardness systematically measured with respect to ageing time and oxygen concentration suggests that α2 precipitation is not the dominant hardening mechanism during ageing. Graphical abstract: Image, graphical abstract